PERANCANGAN SISTEM INFORMASI PENJUALAN PADA ZENIS PETSHOP BERBASIS WEB - Widiyansyah Nur, Raihan (Universitas Majalengka, 2022)
Zenis Petshop is a business in the field of providing needs and services for pets. In its business, Zenis Petshop sells various pet needs ranging from cat food, dogs, hamsters, cages, etc. In addition to selling a variety of food and accessories, Zenis Petshop also offers grooming services or an animal salon specifically for cats, such as grooming, bathing, and cutting nails. The problems faced by Zenis Petshop include problems in processing goods data that are still not computerized, there is no evidence of transactions such as proof of sales. Another problem that exists at Zenis Petshop is that they often have difficulty checking stock of goods, there is no sales report and they only use a recap of notes for reports. To be able to overcome these problems, we need an information system that can help processing data items, sales and profit reports by combining components that have not been computerized into one system. with the creation of a web-based sales information system using the waterfall method so that later it can be used in its business processes to be more effective and fast.